Optimization analysis of stiffness and natural frequency of unidirectional and randomly oriented short fiber-reinforced composite materials - Onyibo, Emmanuel Chukwueloka; Gazioglu, Aysegul; Abulibdeh, Mohammad; Osman, Osman Mohamed; Huwail, Turki Bin; Alkhatib, Mohammed; Safaei, Babak (Springer Wien, 2025)
In this study, numerical and analytical techniques including finite element analysis (FEA), rule of mixture (ROM), and Halpin-Tsai model were used to study the effects of the fiber volume fraction (FVF) on the vibrational responses of microscale unidirectional (UD) and random short fiber-reinforced (RSFR) finite element (FE)-modeled composite unit cells. It was found that as the FVF increases, so do the strength, resistance to deformation (stiffness), and natural frequency of the fiber-reinforced composite. However, such improvements have also shown to cause an increase in the overall mass of the composites, due to higher FVFs, and therefore, resulting in the exhibition of an early fiber-matrix debonding potential. The results of the simulation showed that the optimal dynamic stability was attained for a FVF of 0.3, and the maximum resistance to deformation with respect to stiffness-to-mass ratio was achieved for a FVF of 0.2. These results highlight the importance of selecting optimum FVFs for achieving the best balance between the desired performance (stiffness-to-mass) and mechanical properties of unidirectional fiber-reinforced composites (UD-FRC) and RSFR composites. Also, the harmonic loading capabilities of the hybrid composites having optimized FVFs were equally investigated.
Keywords: Mechanical-Properties; Vibration; Behavior; Length